Predictors of the early introduction of solid foods in infants: results of a cohort study - Scott, Jane; Binns, Colin; Graham, Kathleen; Oddy, W. (BioMed Central, 2009)
Background: The early introduction of solid foods before 4 months of age has been associated with an increased risk of diarrhoea in infancy and a greater risk of wheeze and increased percentage body fat and weight in childhood. The purpose of this study was to identify the level of compliance with national recommendations related to the timing of the introduction of solid foods and to describe the maternal and infant characteristics associated with the timing of the introduction of solids. Methods: Subjects were 519 participants in the second longitudinal Perth Infant Feeding Study (PIFS II) recruited from two maternity hospitals in Perth, Western Australia in 2002/3. Data collected prior to, or shortly after discharge from hospital, and at 4, 10, 16, 22, 32, 40 and 52 weeks postpartum included timing of the introduction of solid foods and a variety of maternal and infant characteristics associated with the introduction of solid foods. Multivariate logistic regression was used to identify those factors associated with the risk of introducing solid foods early, which for the purposes of this study was defined as being before 17 weeks.Results: The median age of introduction of solid foods was 17.6 weeks. In total, 44% of infants had received solids before 17 weeks and 93% of infants had received their first solids before 26 weeks of age. The strongest independent predictors of the early introduction of solids were young maternal age, mother smoking prior to pregnancy and not fully breastfeeding at 4 weeks postpartum. In general, mothers introduced solids earlier than recommended because they perceived their baby to either need them or be ready for them. Conclusion: This study showed a high level of non-compliance among Australian mothers with the infant feeding recommendation related to the timing of solids that was current at the time. In order to improve compliance health professionals need to be aware of those groups least likely to comply with recommendations and their reasons for non-compliance. Infant feeding recommendations need to be evidence-based, uniformly supported by professionals and widely, clearly and consistently articulated if higher rates of compliance are to be achieved in the future.